SENI PERTUJUKAN TARI NTAK KUDO PADA MASYARAKAT RAWANG KECAMATAN HAMPARAN RAWANG KOTA SUNGAI PENUH PROVINSI JAMBI - Fitriani '; Drs. Ridwan Melay, M.Si; Drs. Kamaruddin Oemar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This paper discusses the art of dance performances in public Ntak Kudo Rawang District Hamparan Rawang of Sungai Penuh City of Jambi Province. Performing arts dance Kudo merupan not one dance Rawang community which belongs to the art of dance culture. Kudo had no dance as entertainment functions Rawang community. Dance kudo can not dance danced by the young and old, there is no age limit. The aim of this study was to determine and explain the art of dance and the Kudo not prndorong existence in the era of globalization. This research was conducted using the method of history or historical. Data were collected through library research techniques, observation, documentation and interview. Data were analyzed with descriptive method, historical kompratif, and qualitative analysis. The results showed that the art of dance performance plot Kudo has an important role in a culture Rawang District Hamparan Rawang of Sungai Penuh City Jambi Province, the art is unbelievable displayed in traditional events of Rawang, such as coming of age rituals tradition wedding, banquet Sko (Heritage), customs Birthplace and traditional coming of age rituals. Each end of the ceremonial dance Ntak Kudo shown. So, dance Ntak Kudo is a dance culture and the identity of local communities. Kudo not dance very popular community and create a movement that is easily imitated dance Ntak Kudo be able to maintain its existence in the middle of globalization today.Keywords: Cultural dance, Ntak Kudo.